2021
DOI: 10.1021/acs.jmedchem.0c02051
|View full text |Cite
|
Sign up to set email alerts
|

Potent Lys Patch-Containing Stapled Peptides Targeting PCSK9

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9), identified as a regulator of low-density lipoprotein receptor (LDLR), plays a major role in cardiovascular diseases (CVD). Recently, Pep2-8, a small peptide with discrete three-dimensional structure was found to inhibit the PCSK9/LDLR interaction. In this paper, we describe the modification of this peptide by using stapled peptide and SIP technologies. Their combination yielded potent compounds such as 18 that potently inhibited the binding of PCSK9 to LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Focusing on the PPIs of p53/HDM2 and Bcl-2 family, hydrocarbon-mediated anticancer stapled peptides have been reported . Also, this strategy has found its application as inhibitors for epidermal growth factor receptor, for estrogen receptor/coactivator interaction and also in various other aspects. Although the stapling strategy in different PPIs interface sites has been explored for designing potential inhibitors, the application of this strategy to control microtubule dynamics has not yet been explored. Toward this direction, the article demonstrates, for the first time, an in silico approach to design α-helical peptides from hot spots of the tubulin interface followed by their stapled version to inhibit the tubulin–tubulin interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the PPIs of p53/HDM2 and Bcl-2 family, hydrocarbon-mediated anticancer stapled peptides have been reported . Also, this strategy has found its application as inhibitors for epidermal growth factor receptor, for estrogen receptor/coactivator interaction and also in various other aspects. Although the stapling strategy in different PPIs interface sites has been explored for designing potential inhibitors, the application of this strategy to control microtubule dynamics has not yet been explored. Toward this direction, the article demonstrates, for the first time, an in silico approach to design α-helical peptides from hot spots of the tubulin interface followed by their stapled version to inhibit the tubulin–tubulin interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Modification approaches for Pep2-8 include 1-amino-4-phenylcyclohexane-1-carbonyl extension (~ 100-fold increase in affinity) (Burdick et al 2020 ), conjugation with antagonistic peptides that can bind to the N-terminal groove of PCSK9 (20-fold increase in potency) (Zhang et al 2017 ), and bioactive cyclization via various linkers (∼ 100-fold higher activity) (Tombling et al 2021 ). In addition, Bourbiaux et al reported novel analogs with 1000-fold better affinity than Pep2-8 using stapling as well as the addition of charged aa (Lys) to induce the helical conformation of Pep2-8 and thus protect it from enzymatic degradation (Bourbiaux et al 2021 ).…”
Section: Current Strategies Of Therapeutic Peptides In Cadmentioning
confidence: 99%
“…(A) The crystal structure of the complex of Pep2-8 ( 22 ) with the PCSK9 indicates an acidic patch on the surface of PCSK9 (in red, PDB ID: 4NMX). Adapted from ref . Copyright 2021 American Chemical Society.…”
Section: Preclinical Pcsk9-targeted Peptidesmentioning
confidence: 99%
“…A potent disruptor of the PCSK9:LDLR interaction was identified by employing stapled peptide and structure-inducing probes (SIP) technology to modify the Pep2-8 peptide (22). 151 Initially, the acidic (negatively charged) patch (Glu159, Asp343, Glu366, and Asp367) on the surface of Table 4. continued PCSK9 located near the C-terminal of Pep2-8 (less than 20 Å) was discovered by analyzing the crystal structure of the Pep2-8:PCSK9 complex (Figure 14A, PDB ID: 4NMX).…”
Section: Preclinical Pcsk9-targeted Peptidesmentioning
confidence: 99%